Phosphorus Mobilization from Manure‐Amended and Unamended Alkaline Soils to Overlying Water during Simulated Flooding. Issue 4 (1st July 2015) - Amarawansha, E. A. G. S.; Kumaragamage, D.; Flaten, D.; Zvomuya, F.; Tenuta, M.
Abstract : Anaerobic soil conditions resulting from flooding often enhance release of phosphorus (P) to overlying water. Enhanced P release is well documented for flooded acidic soils; however, there is little information for flooded alkaline soils. We examined the effect of flooding and anaerobic conditions on P mobilization using 12 alkaline soils from Manitoba that were either unamended or amended with solid cattle manure. Pore water and floodwater were analyzed over 8 wk of simulated flooding for dissolved reactive P (DRP), Ca, Mg, Fe, and Mn. As expected, manured soils had significantly greater pore and floodwater DRP concentrations than unamended. Flooding increased pore water DRP concentrations significantly in all soils and treatments except one manured clay in which concentrations increased initially and then decreased. Floodwater DRP concentrations increased significantly by two‐ to 15‐fold in 10 soils regardless of amendment treatment but remained relatively stable in the two soils with greatest clay content. Phosphorus release at the onset of flooding was associated with the release of Ca, Mg, and Mn, suggesting that P release may be controlled by the dissolution of Mg and Ca phosphates and reductive dissolution of Mn phosphates. Thereafter, P release was associated with release of Fe, suggesting the reductive dissolution of Fe phosphates. Differences in pore water and floodwater DRP concentrations among soils and amendment treatments and the high variability in P mobilization from pore water to floodwater among soils indicate the need to further investigate chemical reactions responsible for P release and mobility under anaerobic conditions.